Decreased expression of the m6A RNA methyltransferase METTL3 is associated with residual ridge resorption - Harini Sri Krishnamoorthy; Balachander Kannan; Dhanraj Ganapathy; Vijayashree Priyadharsini Jayaseelan; Paramasivam Arumugam (Journal of Oral Biology and Craniofacial Research)
Objective: N6-methyladenosine (m6A) methylation and its regulators play crucial roles in the progression of osteoporosis (OP) by regulating the expression of osteoporosis-related genes. In this study, we have analyzed the expression of methyltransferase-like 3 (METTL3) and its target gene Runt-related transcription factor 2 (RUNX2) in patients with residual ridge resorption (RRR). Materials and methods: A total 50 number of participants were included in this comparative study (RRR – n25 and healthy control – n25). Total RNA was extracted from peripheral blood and converted into cDNA. METTL3 and RUNX2 expression levels were quantified using RT-qPCR with GAPDH as the reference gene. Bioinformatics tools were used to identify gene functions and pathways. Results: Real-time polymerase chain reaction (qPCR) revealed that METTL3 and RUNX2 expression was downregulated in the RRR group compared to that in healthy controls (P < 0.05). In silico functional analysis provided information regarding the role of METTL3 in various biological processes. Conclusion: Our findings suggest that METTL3 dysregulation contributes to RRR pathogenesis. Further large-scale samples and functional studies are required to identify their therapeutic potential.